2006
DOI: 10.1111/j.1553-2712.2006.tb01725.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Performance Improvement Methods to Enhance Emergency Department Patient Satisfaction in the United States: A Critical Review of the Literature and Suggestions for Future Research

Abstract: There is modest evidence supporting a range of performance improvement interventions for improving ED patient satisfaction. Further work is needed before specific, evidence-based recommendations can be made regarding which process changes are most effective. Recommendations are made for improving the quality of performance improvement efforts in the ED setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Adequate representation is critical to identifying the full range of what needs to be measured and to avoiding measures that will influence behaviors in negative unintended ways. The actors’ confidence and trust in the validity of the measures. This is achieved by selecting metrics that are seen to accurately capture what is intended to be measured (e.g., identifying a metric that both clinicians and patients agree actually measures “patient‐centeredness”) (Boudreaux, Cruz, and Baumann 2006; Burstrom 2009; Conway et al 2006). The actors’ understanding of “what the numbers mean” (including a nuanced understanding of what a change—or lack of change—in a particular metric signifies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate representation is critical to identifying the full range of what needs to be measured and to avoiding measures that will influence behaviors in negative unintended ways. The actors’ confidence and trust in the validity of the measures. This is achieved by selecting metrics that are seen to accurately capture what is intended to be measured (e.g., identifying a metric that both clinicians and patients agree actually measures “patient‐centeredness”) (Boudreaux, Cruz, and Baumann 2006; Burstrom 2009; Conway et al 2006). The actors’ understanding of “what the numbers mean” (including a nuanced understanding of what a change—or lack of change—in a particular metric signifies).…”
Section: Resultsmentioning
confidence: 99%
“…The actors’ confidence and trust in the validity of the measures. This is achieved by selecting metrics that are seen to accurately capture what is intended to be measured (e.g., identifying a metric that both clinicians and patients agree actually measures “patient‐centeredness”) (Boudreaux, Cruz, and Baumann 2006; Burstrom 2009; Conway et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review found weak evidence that observation units reduce the length of stay and reduce admissions [12]. It has been shown that short stay units improve patient satisfaction and quality of life [13,14]. …”
Section: Discussionmentioning
confidence: 99%
“…Boudreaux et al. () further provided the theoretical foundation that patient satisfaction is dependent on physician performance. Therefore, as a physician's ability to speed up processing or handle more complex patients is associated with high RVUs/hr Index, we posit that physicians with high RVUs/hr Index will exhibit better PG scores relative to their peers (see the right‐side of Figure b).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Together, we anticipate that as a physician's productivity (RVUs/hr = RVUs/Patients 9 Patients/Hr) increases, patients will perceive that the physician is both highly skilled and focused, leading to higher PG percentile rank scores (hereafter abbreviated as PG scores), resulting in a higher PG Index. Boudreaux et al (2006) further provided the theoretical foundation that patient satisfaction is dependent on physician performance. Therefore, as a physician's ability to speed up processing or handle more complex patients is associated with high RVUs/hr Index, we posit that physicians with high RVUs/hr Index will exhibit better PG scores relative to their peers (see the right-side of Figure 2b).…”
Section: Factors Impacting Physician Performancementioning
confidence: 99%